Development of Audio Visual Media to Improve Science Learning Outcomes of Grade V Elementary School Students - Rika Yuliana; Trio Erawati Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students in science learning activities still get low results. Student motivation is relatively low because the presentation of material in learning activities is very monotonous because teachers do not make enough use of supportive learning media. This research aims to develop audio-visual media in improving the science learning outcomes of grade V elementary school students. This type of research uses development research with a 4D model which includes 4 stages, namely define, design, develop, and disseminate. The research sample was 67 elementary school students in class V. After development, the audio-visual media was tested for feasibility by three experts, namely linguists, materials and media experts, then the media would be disseminated or implemented to obtain data on student learning outcomes by collecting data using pre-test and post-test. The data analysis technique uses SPSS to test normality, n-gain and the T-Test pired sample test to find out how effective and how much difference student learning outcomes are in science learning. The results showed that the audio-visual media obtained an N-Gain value of 82.43 with the effective category and the T test result of <.001 which means that there is a significant difference between before and after treatment.